Mechanisms of penetration in polyethylene reinforced cross-ply laminates. (December 2015) - O'Masta, M.R.; Crayton, D.H.; Deshpande, V.S.; Wadley, H.N.G.
Abstract: The mechanisms of progressive penetration for two ultrahigh molecular weight polyethylene (UHMWPE) reinforced laminates have been investigated. One used an UHMWPE fiber reinforcement while the other utilized molecularly aligned tape. Both materials had similar out of plane compressive strengths, but the fiber system had a 40% higher in plane tensile strength than the tape. Laminated, 6 mm thick plates with a [0°/90°] ply architecture were impacted by a 12.7 mm diameter sphere under conditions that either allowed out of plane plate deflection or eliminated this deflection by rear support of the target. The depth of penetration and the ballistic limit in the rear-supported tests were identical for the two materials, and proceeded by progressive ply failure. However, tests in the edge clamped condition resulted in a substantially higher penetration resistance, especially for the higher tensile strength fiber-reinforced material. Edge clamped testing of a bilayer target, where the front third was composed of the tape material and the remainder comprised fiber reinforced laminate, had the same ballistic limit as a target composed of only the higher ply tensile strength fiber reinforced material. Penetration in both test support conditions was discovered to occur by tensile ply rupture under the projectile, consistent with a recently proposed mechanism for converting out of plane compression to in plane ply tension. Lateral displacement of plies was also observed near the sides of impact craters in both materials, indicating the existence of a second mechanism impeding penetration of the spherical shaped projectile. Highlights: A fiber and a solid-state tape UHWMPE laminate are impacted by a hard sphere. Laminates fail progressively by tensile rupture and lateral displacement of ply. Without deflection, penetration is governed by the compressive resistance. With deflection, impact performance was increased and was higher for higher tensile strength grade. A fiber/tape bilayer laminate shows potential benefits to hybrid targets.